The Hypercontent-Based Interactive Multimedia in Problem-Based Learning to Improve Indonesian Language Learning Outcomes of Grade IV Elementary School Students - Putri Nugraheni; Isa Ansori (Universitas Pendidikan Ganesha, 2025)
This research was motivated by the low learning outcomes of fourth-grade elementary school students in Indonesian language subjects, particularly in narrative text material. This issue is caused by a lack of learning motivation, unengaging learning media, and suboptimal implementation of learning models. The purpose of this study is to develop Hypercontent-based interactive multimedia within the Problem Based Learning (PBL) model to improve Indonesian language learning outcomes. This study is a type of Research and Development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were fourth-grade students, involving 9 students in a small-scale trial and 23 students in a large-scale trial. Data collection methods included observations, interviews, teacher and student needs questionnaires, and validation questionnaires from material experts, media experts, teachers, and students. Data analysis techniques were carried out using qualitative descriptive methods to assess media feasibility, while the effectiveness test was conducted using the correlated t-test analyzed through the SPSS application. The Hypercontent-based interactive multimedia was validated by expert teams, indicating that the media was highly feasible for use, with a score of 95% from material experts and 93.33% from media experts. The trials showed an improvement in learning outcomes, with teacher responses reaching 98% and student responses 76%. Therefore, it can be concluded that Hypercontent-based interactive multimedia is theoretically, practically, and pedagogically effective in improving learning outcomes, assisting teachers, and supporting students’ narrative writing skills.